Simulation study of proton beam extraction process based on CST software - Renli Zhu; Yuzhong Qian; Hui Li; Lizhen Liang (AIP Advances)
The beam extraction system is a crucial component of the ion source system of an accelerator that significantly influences the quality of the beam and determines the transmission efficiency of the subsequent structures. Based on the particle tracking solver of the CST software, which can simulate the 3D states of beam transmission, this study investigates multiple parameters that affect ion optics, such as plasma density and electrode structure. The reasons for the corresponding beam states were analyzed according to the results of theoretical simulations. The aim of this simulation is to optimize the design of the extraction system and provide guidance for analyzing experimental operation faults.